2001
DOI: 10.1111/j.1346-8138.2001.tb00152.x
|View full text |Cite
|
Sign up to set email alerts
|

Successful Treatment of a Patient with Lymphomatoid Papulosis by Methotrexate

Abstract: We report a case of lymphomatoid papulosis (LyP) that occurred in a 44-year-old Japanese male patient. Reddish papules with a small number of pustules and nodules were observed on the extremities, chest and upper back. Most lesions were also associated with central necrosis, ulceration and crusting, and regressed spontaneously within 4 to 6 weeks. Histopathological examination revealed wedge-shaped dense cellular infiltrate in the dermis, which was mixed with large atypical lymphoid cells, small lymphocytes, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 23 publications
0
6
0
2
Order By: Relevance
“…MTX has been used for treating lymphomatoid papulosis, pityriasis lichenoides and palmoplantar pompholyx, but evidence for its efficacy is limited to case reports. Other possible indications supported by case reports include oral lichen planus, dermatomyositis, cutaneous vasculitis (including cutaneous polyarteritis nodosa, Behçet disease and erythema elevatum diutinum), pyoderma gangrenosum, necrobiosis lipoidica, granuloma annulare, alopecia areata, chronic idiopathic urticaria, Hailey‐Hailey disease and Langerhans cell histiocytosis …”
Section: Indicationsmentioning
confidence: 99%
“…MTX has been used for treating lymphomatoid papulosis, pityriasis lichenoides and palmoplantar pompholyx, but evidence for its efficacy is limited to case reports. Other possible indications supported by case reports include oral lichen planus, dermatomyositis, cutaneous vasculitis (including cutaneous polyarteritis nodosa, Behçet disease and erythema elevatum diutinum), pyoderma gangrenosum, necrobiosis lipoidica, granuloma annulare, alopecia areata, chronic idiopathic urticaria, Hailey‐Hailey disease and Langerhans cell histiocytosis …”
Section: Indicationsmentioning
confidence: 99%
“…There is no curative therapy for LyP, so the main goal of the management is to control symptoms and maintain the clinical response to improve quality of life. Several studies 22,23 demonstrated that low-dose methotrexate sodium (10–15 mg or less given weekly) is an effective and well-tolerated treatment for LyP. Systemic multiagent chemotherapy provides a response rate comparable to that of a low dose of methotrexate (86.7% and 87.5%, respectively).…”
Section: Commentmentioning
confidence: 99%
“…1 Phototherapy is also a viable and well-tolerated therapy for lymphomatoid papulosis 2 ; however, it is temporally and geographically restrictive and therefore not an option for many patients. The course of the disease is susceptible to systemic immunosuppressive agents, and good treatment success has been reported with MTX.…”
Section: Case Reportmentioning
confidence: 99%